Моделювання ланцюга постачання в транспортно-логістичній системі - Аулін, Віктор; Великодний, Денис; Дьяченко, Вікторія (Посвіт, 2019)
It is determined that simulation is an effective tool for solving problems of analysis and synthesis of the supply chain in the transport and logistics system. It is shown that the types of resources in them are mobile objects.
Modeling of transport and logistics supply chain
Keywords: 164; 656